From Samuel Beckett to Nancy Huston: a poetics of self-translation - Sandra Regina Goulart Almeida; Julia de Vasconcelos Magalhães Veras (Ilha do Desterro)
This article focuses on self-translation and bilingualism as an essential characteristic to understand Samuel Beckett’s and Nancy Huston’s works and their literary projects. This analysis leads us to think in terms of a broader perspective of the term translation, which psychoanalysis and contemporary literary studies have addressed. Beckett had a literary project, which included a subversion of language that he aimed at through the process of self-translation. More than an activity, the process of translation and the manipulation of two languages is part of his poetic inspiration. When Huston makes an explicit homage to Beckett and puts herself in the same experience of writing in a foreign language and translating her own texts, she gives a testimony, and also provides a key for reading Beckett from a contemporary perspective. Despite the remarkable differences between these two authors, we claim that self-translation is part of their literary project, and is more than a random event for both of them.